2014
DOI: 10.1016/j.neuroscience.2014.04.069
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated orexinergic signaling underlies depression-like responses induced by daytime light deficiency

Abstract: Light has profound effects on mood, as exemplified by seasonal affective disorder (SAD) and the beneficial effects of bright light therapy. However, the underlying neural pathways through which light regulates mood are not well understood. Our previous work has developed the diurnal grass rat, Arvicanthis niloticus, as an animal model of SAD (Leach et al., 2013a, Leach et al., 2013b). By utilizing a 12:12hr Dim Light:Dark (DLD) paradigm that simulates the lower light intensity of winter, we showed that the ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 82 publications
6
55
1
1
Order By: Relevance
“…Using the diurnal Nile grass rats, we and others have observed depression- and anxiety-like behaviors in winter-like lighting conditions, i.e. short photoperiods [4, 18] or daytime dim lighting [7, 17]. Furthermore, we found that hypothalamic neurons containing the neuropeptide orexin are likely to play a role in mediating the effects of light on mood and anxiety.…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations
“…Using the diurnal Nile grass rats, we and others have observed depression- and anxiety-like behaviors in winter-like lighting conditions, i.e. short photoperiods [4, 18] or daytime dim lighting [7, 17]. Furthermore, we found that hypothalamic neurons containing the neuropeptide orexin are likely to play a role in mediating the effects of light on mood and anxiety.…”
Section: Introductionsupporting
confidence: 52%
“…Forced swim test and sweet solution preference test were conducted following the first two daily injections as described in a previous study [7]. Following 5 daily injections of either SB-334867 or vehicle, animals (n = 6/group) were sacrificed between ZT 7–8.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…With regards to biological/molecular mechanisms, bright light therapy was reported to increase 5-HT levels in the anterior cingulate and prefrontal cortex by reducing 5-HT transporter binding (Harrison et al, 2014); inhibit orexinergic signaling underlies depression-like responses induced by daytime light deficiency (Deats et al, 2014) and regulate circadian (Lewy et al, 2006).…”
Section: Discussionmentioning
confidence: 99%